ANALYSIS OF ASPECTS OF FOOD SECURITY: A STRATEGIC ANALYSIS OF APPROACH TO SUSTAINABLE FOOD CONSUMPTION PATTERNS AS AN EFFORT TO REALIZE FOOD POLICY IN INDONESIA - Faradilla, Cut; Zulkarnain, Zulkarnain; Bagio, Bagio (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Adequacy of basic food is the desire of all parties, both the government and society as a whole in the economic system. Furthermore, food plays a very high role in the formation of quality human resources. For this reason, a strategy is needed to achieve food security that can realize the availability of food in sufficient quantity and quality, distributed at affordable prices and safe for consumption for every citizen. This study focuses on the strategy of consumption patterns for food improvement in Indonesia. The purpose of this study is to analyze the classification of food security and the share strategy of sustainable food consumption patterns according to important food groups to realize food policy in Indonesia. The object of research includes the level of food consumption according to important food groups per capita and the level of nutritional adequacy. The research method is based on quantitative descriptive statistical analysis method in which all data are collected, grouped and analyzed according to the needs of the research objectives. The results show that the classification of food security in Indonesian society is in the normal category based on the level of energy consumption and the level of protein consumption, which is greater than the recommended nutritional consumption and the percentage level of nutritional adequacy. Strategy analysis with the share approach of Indonesian people's food consumption patterns based on the results of the study shows that consumption patterns according to important food groups have a uniform pattern, with the composition of the dominant important food commodities, namely local rice/glutinous rice, chicken eggs/village and sugar with an average change in consumption per capita of 1.53 and a decrease in consumption patterns from 2018-2021 so that the share strategy for sustainable food consumption patterns that can be used is variety of staple foods and increasing consumption patterns of strategic staple foods. Based on the basic food variation strategy and increasing consumption patterns, the food policies that can be implemented are policies that are relevant to the food security strategy. 53 and a decrease in consumption patterns from 2018-2021 so that the share strategy for sustainable food consumption patterns that can be used is a variety of staple foods and an increase in strategic staple food consumption patterns. Based on the basic food variation strategy and increasing consumption patterns, the food policies that can be implemented are policies that are relevant to the food security strategy. 53 and a decrease in consumption patterns from 2018-2021 so that the share strategy for sustainable food consumption patterns that can be used is a variety of staple foods and an increase in strategic staple food consumption patterns. Based on the basic food variation strategy and increasing consumption patterns, the food policies that can be implemented are policies that are relevant to the food security strategy.